Epistatic role of the MYH9/APOL1 region on familial hematuria genes. - Konstantinos Voskarides; Panayiota Demosthenous; Louiza Papazachariou; Maria Arsali; Yiannis Athanasiou; Michalis Zavros; Kostas Stylianou; Dimitris Xydakis; Eugenios Daphnis; Daniel P Gale; Patrick H Maxwell; Avraam Elia; et al. (PLoS ONE)
Familial hematuria (FH) is explained by at least four different genes (see below). About 50% of patients develop late proteinuria and chronic kidney disease (CKD). We hypothesized that MYH9/APOL1, two closely linked genes associated with CKD, may be associated with adverse progression in FH. Our study included 102 thin basement membrane nephropathy (TBMN) patients with three known COL4A3/COL4A4 mutations (cohort A), 83 CFHR5/C3 glomerulopathy patients (cohort B) with a single CFHR5 mutation and 15 Alport syndrome patients (cohort C) with two known COL4A5 mild mutations, who were categorized as "Mild" (controls) or "Severe" (cases), based on renal manifestations. E1 and S1 MYH9 haplotypes and variant rs11089788 were analyzed for association with disease phenotype. Evidence for association with "Severe" progression in CFHR5 nephropathy was found with MYH9 variant rs11089788 and was confirmed in an independent FH cohort, D (cumulative p value = 0.001, odds ratio = 3.06, recessive model). No association was found with APOL1 gene. Quantitative Real time PCR did not reveal any functional significance for the rs11089788 risk allele. Our results derive additional evidence supporting previous reports according to which MYH9 is an important gene per se, predisposing to CKD, suggesting its usefulness as a prognostic marker for young hematuric patients.